Characterization of the alimentary canal of the aphidophagous ladybird, Adalia bipunctata (Coleoptera: Coccinellidae): anatomical and histological approaches. Issue 1 (13th May 2014) - Borges, Isabel; Nóia, Marlene; Camarinho, Ricardo; Rodrigues, Armindo S.; Soares, António O.
Abstract The alimentary canal of the two‐spot ladybird Adalia bipunctata (Linnaeus) (Coleoptera: Coccinellidae) presents the foregut (stomodeum), the midgut (mesenteron) and the hindgut (proctodeum). The shortest region is the foregut and the longest is the midgut. The relative proportions of the main regions were found to be similar for males and females. In the foregut it was possible to distinguish the pharynx, the esophagus and the proventriculus but no crop. The hindgut is composed of the ileum, rectum and rectal canal. Generally the organ width is similar for males and females, but females presented a wider proventriculus. The epithelium of the foregut varied from squamous to simple cuboidal and columnar. In the midgut the epithelium is simple columnar with goblet and regenerative cells. The epithelium of the hindgut varied from simple cuboidal to squamous. Females presented thicker midgut epithelium whereas males presented thicker epithelium in the esophagus. The anatomy of the alimentary canal of A. bipunctata seems to conform to its carnivorous and recent phylogenetic status within the family Coccinellidae.